Réponses

2013-03-21T20:47:25+01:00

a. 5x=3x+1

5x-3x=1

2x=1

x=1/2

x=0.5

 

b.8x=12x+4

8x-12x=4

-4x=4

x=4/-4

x=-1

 

c. 4-7y=10y

-7y-10y=-4

-17y=-4

y=-4/-17

y=4/17

 

d. 7x+1=-4-x

7x+x=-4-1

8x=-5

x=-5/8

 

e. 2+3x=7-3x

3x+3x=7-2

6x=5

x=5/6

 

f.5+6x=-x-9

6x+x=-9-5

7x=-14

x=-14/7

 

g. 11x+3=8x+7

11x-8x=7-3

3x=4

x=4/3

 

h. 5.5x+1.5=9x+6

5.5x-9x=6-1.5

-3.5x=4.5

x=4.5/-3.5

 

i. 7-3.3x=2x-9.7

-3.3x-2x=-9.7-7

1.3x=-16.7

x=-16.7/1.3

 

j. 5.1-x=-8x+1.7

-x+8x=1.7-5.1

7x=-3.4

x=-3.4/7